Seasons of life the biological rhythms that enable living things to thrive and survive - Foster, Russell G.; Kreitzman, Leon (Yale University Press, 2009)
Just as daily events are timed by living creatures through circadian rhythms, so seasonal events are timed through an internal calendar that signals birds to return to nesting grounds, salmon to spawn, plants to flower, squirrels to hibernate, kelp to stop growing. Russell G. Foster and Leon Kreitzman draw on remarkable recent scientific advances to explain how seasonal change affects organisms, and how plants and animals over countless generations have evolved exquisite sensitivities and adaptations to the seasons. The authors also highlight the impact of seasonal change on human health and well-being. They conclude with a discussion of the dangers posed when climate changes disrupt the seasonal rhythms on which so much life depends